1999
DOI: 10.1056/nejm199906103402302
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tissue Plasminogen Activator for Acute Ischemic Stroke at One Year

Abstract: During 12 months of follow-up, the patients with acute ischemic stroke who were treated with t-PA within three hours after the onset of symptoms were more likely to have minimal or no disability, than the patients given placebo. These results indicate a sustained benefit of t-PA for such patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
176
1
2

Year Published

2000
2000
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 557 publications
(186 citation statements)
references
References 23 publications
7
176
1
2
Order By: Relevance
“…Independence in these activities enables the stroke patient to be discharged home without being too dependent on others. With respect to basic functional outcome, our findings replicate and extend a previous study on the benefit of rt-PA at 6 and 12 months post-stroke [3].…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Independence in these activities enables the stroke patient to be discharged home without being too dependent on others. With respect to basic functional outcome, our findings replicate and extend a previous study on the benefit of rt-PA at 6 and 12 months post-stroke [3].…”
Section: Discussionsupporting
confidence: 88%
“…Similar treatment effects have been found after six months and one year poststroke [3]. The benefit of rt-PA is thought to be due to the early recanalisation of occluded arteries, resulting in increased cerebral reperfusion [4] and a subsequent reduction of lesion volume [5].…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…The results of our study group have also indicated that thrombolysis has a favorable effect on visuoperceptual functions in acute RH stroke (Laihosalo et al, forthcoming). Several other studies also suggest that thrombolysis improves the functional outcome of stroke patients concerning basic activities of daily living (ADL) (Kwiatkowski et al, 1999;Lindsberg et al, 2003;Lansberg, Schrooten, Bluhmki, Thijs, & Saver, 2009; The National Institute of Neurological Disorders and Stroke rt-PA Stroke Study Group, 2 LOSOI ET AL. 1995), which include activities like feeding, dressing, bathing, and toileting (Kelly-Hayes, Robertson, Broderick, Duncan, & Hershey, 1998).…”
mentioning
confidence: 99%